Effect of Substrate on One-Dimensional Multiferroic Properties - Ivan Maltsev; Igor Bychkov (Magnetochemistry, 2022)
We present a theoretical study of the substrate influence on the electrical and magnetic properties of a one-dimensional multiferroic. We used a one-dimensional axial next-nearest neighbor Ising model (1D ANNNI model). The effect of the substrate was modeled using the periodic Frenkel–Kontorova potential. It is shown that the periodic potential of the substrate reduces the polarization of the multiferroic at low temperatures. The substrate potential significantly affects the structural changes near the magnetic phase transition temperature.